Malaria, tuberculosis and HIV: what's new? Contribution of the Institut Hospitalo-Universitaire Méditerranée Infection in updated data - Almeras, Lionel (New Microbes New Infect, 2018)
The Institut Hospitalo-Universitaire Méditerranée Infection is positioned for the diagnosis, prevention and treatment of the ‘big three’ killer diseases: malaria, tuberculosis and HIV. We implemented the use of new diagnostic samples such as stools and new diagnostic tests such as mass spectrometry for the dual identification of vectors and pathogens. Furthermore, advances in the prevention and treatment of malaria and tuberculosis are reviewed, along with advances in the understanding of the role of microbiota in the resistance to HIV infection. These achievements represent a major step towards a better management of the ‘big three’ diseases worldwide.